2021
DOI: 10.3390/molecules26082170
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Microencapsulated or Nanoemulsified Bioactive Compounds Influences the Antioxidant and Antimicrobial Activities of a Fresh Cheese

Abstract: The objective of this study was to compare the effects of the incorporation of microcapsules or nanoemulsions with Opuntiaoligacantha on the quality of fresh cheese. Three treatments were established: Control, cheese with microcapsules (Micro), and cheese with nanoemulsion (Nano). The parameters evaluated were physicochemical (moisture, ash, fat, proteins, and pH), microbiological (mesophilic aerobic bacteria, mold–yeast, and total coliforms), functional (total phenols, flavonoids, and antioxidant capacity), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
1
16
1
1
Order By: Relevance
“…This result confirmed the well-known antioxidant properties of citrus EOs [ 69 ], mainly due to their components such as terpenes and phenolic compounds. For this reason, citrus EOs are commonly incorporated into foods to prevent oxidation, to increase the shelf life and to provide health benefits [ 70 ]. However, the total polyphenols content did not differ significantly among the experimental and control productions.…”
Section: Resultsmentioning
confidence: 99%
“…This result confirmed the well-known antioxidant properties of citrus EOs [ 69 ], mainly due to their components such as terpenes and phenolic compounds. For this reason, citrus EOs are commonly incorporated into foods to prevent oxidation, to increase the shelf life and to provide health benefits [ 70 ]. However, the total polyphenols content did not differ significantly among the experimental and control productions.…”
Section: Resultsmentioning
confidence: 99%
“…The hardness, cohesiveness, chewiness, springiness, and resilience values of the cheese samples were in the ranges of 95.40-150.51 g, 0.25-0.32, 92.32-95.43 g/mm, 6.990-6.995 mm, and 0.07-0.08 mm, respectively. Shamsia and El-Ghannam (2017), and El-Batawy and Soliman (2017) also reported a significant increase in the hardness of ricotta cheese during the storage period Pérez-Soto et al (2021). found that the addition of Opuntia oligacantha microcapsule and nano-emulsion to fresh cheese reduced the hardness and chewiness of cheeses compared to control, but did not have an effect on elasticity and cohesiveness parameters.…”
mentioning
confidence: 95%
“…The color itself is one of the first quality attributes on the basis of which the consumer assesses the acceptability of a product [ 7 ]. According to Pérez-Soto et al [ 40 ], the addition of bioactive compounds may affect the hardness of cheeses, but it has no effect on elasticity, firmness, and chewiness. However, it depends on the type of cheese.…”
Section: Resultsmentioning
confidence: 99%